DYNAMICS OF INDONESIAN LABOR COOPERATION RELATIONSHIP WITH SAUDI ARABIA - Leriche Venisha (Sociae Polites, 2022)
Each country will meet each other and work together to meet the needs of their respective countries. In bilateral relations, Indonesia cooperates through an agreement on the protection and placement of domestic sector workers between the Republic of Indonesia and the Kingdom of Saudi Arabia with an effort to agree on a moratorium on sending Indonesian Migrant Workers (PMI) to Saudi Arabia. The problem discussed in this study is the relationship between Indonesia and Saudi Arabia regarding the protection and legal remedies for Indonesian workers in Saudi Arabia. This research uses normative juridical mode. Methods of collecting information from books, magazines and the internet such as relations between Indonesia and Saudi Arabia. The results show that the governments of Indonesia and Saudi Arabia have agreed on a Memorandum of Understanding (MoU) on the placement and protection of Indonesian Migrant Workers in Saudi Arabia. The effect of the signing of this Memorandum of Understanding is to guarantee the protection of the rights and welfare of Indonesian Migrant Workers who work there. Keywords:Cooperation, Indonesia - Saudi Arabia, Employment, International Law